Karl Marx's thoughts on functional income distribution - a critical analysis - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
Keynes, following the tradition of Marx, argued that all values are created by labour and profits. However, functional income distribution between wages and profits is explained differently. In Marx's explanation of functional income distribution, wages are given as a basket of goods needed for the reproduction needs of the working class. Profits are then the remaining part of income creation. Given the capital stock, the profit rate can be calculated. The paper shows that Marx's explanation of functional income distribution has several theoretical and practical shortcomings. The Keynesian paradigm in the tradition of the original Keynes provides an alternative. Here the profit rate is given by processes in the financial market, and, among other things, by the interest rate. Monopolistic or oligopolistic structures, following the tradition of Kalecki, can also influence the profit rate. In addition, financialisation can push up the profit rate. Given the capital stock the consumption basket of workers depends on the level of productivity and the profit rate explained in a Keynesian and Kaleckian way.
Keywords: B24; B51; E25; 330; Marxism; functional income distribution; Sraffa; Keynesianism